Noncovalent Functionalization of Thiopyridyl Porphyrins with Ruthenium Phthalocyanines. Issue 5 (12th February 2015) - Lourenço, Leandro M. O.; Hausmann, Anita; Schubert, Christina; Neves, Maria G. P. M. S.; Cavaleiro, José A. S.; Torres, Tomás; Guldi, Dirk M.; Tomé, João P. C.
Abstract Preconditions for the design of efficient organic solar‐light‐converting systems are strong absorptions across the visible region, the capacity to funnel excited state energy by intermolecular energy transfer, and alternative association processes in the photoinduced electron transfer. In this context, thiopyridyl porphyrins (PorSPy) and ruthenium phthalocyanines (RuPcs) proved to be versatile building blocks for the construction of novel supramolecular Por–Pc hybrid systems (PorSPy–RuPc) by axial coordination at ruthenium. The thiopyridyl groups placed at the bay region of the porphyrins coordinate the RuPc dye. A notable redistribution of the electron density in the new heterochromophore structures evidences the electron‐donating/‐accepting communication between the two dyes in the supramolecular hybrids. These structural hybrids were investigated physicochemically by means of their ground and excited state reactivities. Photophysical investigation by time‐resolved transient absorption, mainly fluorescence and femtosecond spectroscopy, evidenced efficient intermolecular energy transfer from the photoexcited central porphyrin to the peripheral phthalocyanines in the supramolecular multichromophore ensembles. The findings may give impetus for the design of interesting materials for solar‐light‐converting systems.